2010
DOI: 10.1038/ejcn.2009.156
|View full text |Cite
|
Sign up to set email alerts
|

Total body bone mineral content and density during weight loss and maintenance on a low- or recommended-dairy weight-maintenance diet in obese men and women

Abstract: Background: Diets high in either dairy or calcium during moderate weight reduction both prevent loss of bone mineral density (BMD) and suppress bone turnover. The purpose of this study was to determine whether recommended dairy and calcium intakes during weight maintenance favorably affect total body BMD (TBBMD) and bone mineral content (TBBMC) in obese adults. Methods: Obese men (n ¼ 49) and women (n ¼ 64), aged 40.8 ± 0.6 years, underwent 12 weeks of moderate energy restriction (B1200 kcal/day) followed by 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…This prevented us from being able to assess whether the changes that were observed immediately after finishing the weight-loss diet persisted or resolved once the dietary intervention had ceased. Of the studies that did include a follow-up time point, (21,23,25,27,28,30,39,74) decreases in BMD of the total hip, (23,30,74) lumbar spine, (25,28,30) and total body (21,27,28,30,39) were still present when measured at 3 to 21 months after completion of the dietary weight-loss intervention, raising potential concerns about the long-term impact of repeated weight-loss diets on bone. Hence, it would be important that future studies investigate the longitudinal effects of dietary weight-loss interventions on bone, as in two current trials by our research team.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This prevented us from being able to assess whether the changes that were observed immediately after finishing the weight-loss diet persisted or resolved once the dietary intervention had ceased. Of the studies that did include a follow-up time point, (21,23,25,27,28,30,39,74) decreases in BMD of the total hip, (23,30,74) lumbar spine, (25,28,30) and total body (21,27,28,30,39) were still present when measured at 3 to 21 months after completion of the dietary weight-loss intervention, raising potential concerns about the long-term impact of repeated weight-loss diets on bone. Hence, it would be important that future studies investigate the longitudinal effects of dietary weight-loss interventions on bone, as in two current trials by our research team.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the majority of studies investigated female populations only. In studies where both males and females were included, (20)(21)(22)24,29,42,44,(71)(72)(73)(74)(75) the two sexes were not always reported independently. (22,29,42,44,74) Additionally, although age was reported in all studies, large age ranges prevented us from being able to assign the outcomes to a younger or older population for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 There have also been studies that did not see any changes in 25OHD after weight loss. Hinton et al 37 found no changes in 25OHD levels post-12 weeks of weight loss and, interestingly, it decreased significantly following 24 weeks of weight maintenance. The researchers found a significant season by time interaction, indicating that the change in 25OHD levels was dependent on season during enrolment and suggested seasonal variation may have had a greater impact on 25OHD than changes in weight or fat mass.…”
Section: Do 25-hydroxyvitamin D Levels Change With Weight Loss?mentioning
confidence: 99%